We have an elliptic area defined by $$A := \{(x, y) \in \mathbb{R}^2 \mid (\tfrac{x}{a})^2+(\tfrac{y}{b})^2 \leq 1 \}$$ and a height function $$h \colon \mathbb{R}^2 \to \mathbb{R}, (x, y) \mapsto h(x, y) = c\left[1-(\tfrac{x}{a})^2-(\tfrac{y}{b})^2\right]$$ by transforming the area constraint we get $$y = \pm b\sqrt{1-(\tfrac{x}{a})^2}$$ which gives us the bounds for integrating over the y-axis. By setting $y = 0$ we get the bounds for the x-axis which is $\pm a$.

Finally we can write down our integral $$\int_Ah(x,y)dxdy = \int_{x_1=-a}^{x_2=a} \int_{y_1=-b\sqrt{1-(\tfrac{x}{a})^2}}^{y_2=b\sqrt{1-(\tfrac{x}{a})^2}}c\left[1-(\tfrac{x}{a})^2-(\tfrac{y}{b})^2\right]dydx = \\\ 4c\int_{0}^{x_2} \int_{0}^{y_2}\left[1-(\tfrac{x}{a})^2-(\tfrac{y}{b})^2\right]dydx$$ now comes the hard part.

1. Approach

This was my own attempt which does get stuck at some point

$$\dfrac{8}{3}cb\int_0^a\left[1-(\tfrac{x}{a})^2\right]^\frac{3}{2}dx \stackrel{x = a\sin(z)}{=} \dfrac{8}{3}\dfrac{cb}{a}\int_{z_1=0}^{z_2=a\sin(a)} \left[1-\sin(z)^2\right]^\frac{3}{2}\dfrac{1}{\cos(z)}dz = \dfrac{8}{3}\dfrac{cb}{a}\int_{z_1}^{z_2} \cos(z)^2dz = \dfrac{8}{3}\dfrac{cb}{a}\left[z+\cos(z)\sin(z)\right]\vert^{z_2}_{z_1} = \dfrac{8}{3}\dfrac{cb}{a}\left[a\sin(a)+\cos(a\sin(a))\sin(a\sin(a))\right]$$

2. Approach

This is taken from the solutions.

$$\dfrac{8}{3}cb\int_0^a\left[1-(\tfrac{x}{a})^2\right]^\frac{3}{2}dx \stackrel{x = az}{=} \dfrac{8}{3}cba\int_0^1\left[1-z^2\right]^\frac{3}{2}dz$$

where $\int_0^2\left[1-z^2\right]^\frac{3}{2}dz$ was given with $\dfrac{3}{16}\pi$.


  1. Why does the first approach come to another solution? What rule did I break?

  2. What happened with the substitution $x = az$ in the second approach? How does the a in the upper bound turn to 1 and why is $dz \neq \dfrac{1}{a}$.


1 Answer 1



There were two errors in Approach 1.

First, $dx= a\,\cos z$ and not $\frac1{a\cos z}$.

Second, the upper limit transforms from $x=a$ to $z=\pi/2$.

Then, the integral of interest becomes

$$\frac83 abc\int_0^{\pi/2}\cos^4 z\,dz=\frac83 abc\times \frac{3\pi}{16}=\frac{\pi}{2}abc$$


Here, the substitution $x=az\implies dx=adz$ and when the upper limit on $x$ is $a$, the corresponding upper limit on $z$ is, therefore, $1$ since $a \times 1=a$.

  • $\begingroup$ Could you give more explanation on how $x = a$ to $z = \pi/2$? If $x = a\sin(z)$ then we would need calculate the upper limit with $z = a \iff a\sin(a)$? Same argumentation for the limits in the second approach. $\endgroup$
    – bodokaiser
    Aug 29, 2015 at 7:01
  • $\begingroup$ Sure. So if $x_{upper}=a$ and $x_{upper}=a\sin z_{upper}$, then can you see why $z_{upper}=\pi/2$? Let's solve for $\sin z_{upper}$. It will be $1$. And the sine of $\pi/2$ is indeed $1$. Make sense? $\endgroup$
    – Mark Viola
    Aug 29, 2015 at 7:03
  • $\begingroup$ Ah okay I see. But when I normally use substitution e.g. $\int_0^1 (1-x)^\frac{2}{3}dx$ with $z = 1-x$ then this would yield $x_{upper} = 1-1 = 0$ (what I mean in this case we just "insert" the old limit into the substitution. Your approach tries to find a way how to express the old limit with the new substitution. Why is there this difference? $\endgroup$
    – bodokaiser
    Aug 29, 2015 at 7:09
  • $\begingroup$ Ah I now got the difference. You can do integration by substitution "from the left" or "from the right" this means you either completely substitute e.g. $u = 2x$ or you "wrap the substitution" e.g. $x = \sin u$. Depending on the exact substitution limit transformation must be done differently. I was now stuck the the first type of substitution. $\endgroup$
    – bodokaiser
    Aug 29, 2015 at 7:45

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.